THE SPECIFICS OF SEASIDE HEALTH CARE RESORTS IN POLAND ON THE EXAMPLE OF KAMIEŃ POMORSKI AND MIELNO - Szczepanowska, Ewa; Wodyk, Emilia (Acta Scientiarum Polonorum. Oeconomia, 2010)
Health care resort treatment has a very long history and reaches a deep way back in past time. Health right after the need of thirst and hunger is the most important factor enabling human proper functioning. The purpose of this work is to present and compare, on the example of Kamień Pomorski and Mielno, the offers of seaside health care resorts and indicate that they need restructuring, changes and obtaining new investors. The study was carried out in 120 respondents of both genders, in the age above 18 years old. Respondents consist of a group of two seaside health care resorts within the borders of West Pomeranian district: Kamień Pomorski and Mielno. The testing method included a diagnostic survey regarding a service and holiday offer of a seaside health care resorts. The survey was used to present the adaptation seaside health care resorts to services provided by them, the evaluation of their quality, a customer satisfaction rate and also the direction in which they need to develop and extend their activities. The obtained results allowed observing that Polish health care resorts require high capital investment and restructuring, from resorts infrastructure up to the service offers. Comparing these results with studies of other authors one can consider that health care resorts in Poland are currently not prepared and competitive in comparison with the offers from European countries.